Biotization of in vitro oil palm (Elaeis guineensis Jacq.) and its plant-microbe interactions - Lim, Shey-Li; Subramaniam, Sreeramanan; Baset Mia, Md Abdul; Rahmah, Abdul Rahman Siti; Ghazali, Amir Hamzah Ahmad (Frontiers in Plant Science, 2023)
Continuous discovery of novel in vitro plant culture practices is always essential to promote better plant growth in the shortest possible cultivation period. An alternative approach to conventional micropropagation practice could be achieved through biotization by inoculating selected Plant Growth Promoting Rhizobacteria (PGPR) into the plant tissue culture materials (e.g., callus, embryogenic callus, and plantlets). Such biotization process often allows the selected PGPR to form a sustaining population with various stages of in vitro plant tissues. During the biotization process, plant tissue culture material imposes developmental and metabolic changes and enhances its tolerance to abiotic and biotic stresses, thereby reducing mortality in the acclimatization and pre-nursery stages. Understanding the mechanisms is, therefore crucial for gaining insights into in vitro plant-microbe interactions. Studies of biochemical activities and compound identifications are always essential to evaluate in vitro plant-microbe interactions. Given the importance of biotization in promoting in vitro plant material growth, this review aims to provide a brief overview of the in vitro oil palm plant-microbe symbiosis system.